Kenya's agrifood system: Overview and drivers of transformation - Diao, Xinshen; Pauw, Karl; Smart, Jenny; Thurlow, James (International Food Policy Research Institute, 2023)
The 2010s were a decade of strong economic development in Kenya. Gross domestic product (GDP)—an indicator of the economy’s size—expanded by an average of 5 percent per year (KNBS 2022). This exceeded population growth and helped raise household incomes, leading to a decline in poverty rates and, more importantly, in the number of poor people, for the first time in at least three decades (World Bank 2022). Agriculture played an important role in this. The sector grew alongside the rest of the economy, despite facing many challenges, including climate variability (Ochieng et al. 2020), weak rural infrastructure (Benin and Odjo 2018), shrinking farm sizes (Jayne et al. 2016), and inaccessibility of farm inputs combined with poor agronomic management (Worku et al. 2020). Agriculture, as part of the broader food system, also contributed to growth in downstream or off-farm sectors and helped cushion the economic damage resulting from COVID-19 in 2020 (Pauw, Smart, and Thurlow 2021).